O caráter iniciático da educação filosófica a partir do Fedro de Platão - Magalhães, Bruno Costa (2022)
This research aims to investigate whether Plato had a pedagogical concept for the teaching of Philosophy; and, if so, identify the stages that the disciple went through, according to this conception, until the end of his formation. The investigation is justified insofar as, although Plato has spread, in his work, fragments indicative of the existence of an educational project under construction, he naturally did not point out, systematically, not even in the Republic, the main lines of the formative itinerary that, in part, he absorbed in contact with Socrates. Two hypotheses are tested: that philosophical education, in Plato's view, is a path analogous to that of initiation into the mysteries, practiced in the social environment in which the dialogues were written; and that the Platonic Corpus, if read in this key, provides the researcher with elements to trace the route along which Plato directed those who were personally interested in his philosophical teaching. From the reading of the Platonic dialogues and the Seventh Letter, the investigation also seeks to map, through the commentators, the interpretive tradition on the subject. The backbone of the investigation is the Phaedrus, full of initiatory references, as it is the dialogue that concentrates the largest number of references to Plato's pedagogical conception, with emphasis on the metaphor of the intelligent farmer (Phaedrus 276e). As a result of a careful reading of the Phaedrus, the Seventh Letter, the Apology of Socrates, the Republic, the Symposium, the Phaedo, Theaetetus, the Meno, the Charmides and Alcibiades I, it was possible not only to reinforce the points of contact between the Platonic pedagogy and initiation into the mysteries, but also to relate the main images, allegories and myths that Plato recorded in his work – such as the allegory of the cave and the art of turning around (Republic), the brightness of understanding and the spark (Seventh Letter), the cicadas, the birth of wings, the seeds (Phaedrus), the desire to procreate (Symposium), intellectual pregnancy and the wonder (Theaetetus), the eye that sees itself (Alcibiades I), the enchantment (Charmides), the flight from the world (Phaedo), among others – to each of the three stages of philosophical education identified: (i) philosophical erotica, (ii) dialectical conversation and (iii) unspeakable vision